PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XII IPA SMAN 14 PADANG - Handoko, Viro; Zulfaneti, Zulfaneti; Haryono, Yulia (STKIP PGRI Sumbar, 2013)
The Â comprehension of the mathematical concept students are still low of class XII IPA SMAN 14 Padang becomes problem which is background this research. Other problems that background this research is students tend to ask their friends compared to teachers in the classroom, but the students discussions no effective. One of the solutions that used to overcome such problem is by implementing The Power of Two. The purpose of this research is to know determine whether students comprehension of mathematical concepts by implementing strategies The Power Of Two is better than student comprehension of mathematical concepts with conventional learning class XII IPA SMAN 14 Padang. This research is experimental research with research design randomized on subject. The data analysis used was one way t test by using program MINITAB. Based on the calculation results obtained P-value = 0.001 is smaller than the significance level (Î±) = 0,05 so it can be concluded that the students comprehension of mathematical concepts using strategies The Power Of Two is better than the students comprehension of mathematical concepts with conventional learning class XII IPA SMAN 14 Padang.